Play therapy basics for beginning students - Baggerly, Jennifer; Microtraining Associates (Framingham, MA : Distributed by Microtraining Associates, 2006)
Contains video clips of play therapy sessions with culturally diverse children. The author uses puppets to help communicate the rationale, principles, and basic skills
Title from title screen
Keywords: Play therapy; Cross-cultural counseling